Optically Generated Ultrasound for Intracoronary Imaging - Little, Callum D.; Colchester, Richard J.; Noimark, Sacha; Manmathan, Gavin; Finlay, Malcolm C.; Desjardins, Adrien E.; Rakhit, Roby D. (Frontiers in Cardiovascular Medicine, 2020)
Conventional intravascular ultrasound (IVUS) devices use piezoelectric transducers to electrically generate and receive US. With this paradigm, there are numerous challenges that restrict improvements in image quality. First, with miniaturization of the transducers to reduce device size, it can be challenging to achieve the sensitivities and bandwidths required for large tissue penetration depths and high spatial resolution. Second, complexities associated with manufacturing miniaturized electronic transducers can have significant cost implications. Third, with increasing interest in molecular characterization of tissue in-vivo, it has been challenging to incorporate optical elements for multimodality imaging with photoacoustics (PA) or near-infrared spectroscopy (NIRS) whilst maintaining the lateral dimensions suitable for intracoronary imaging. Optical Ultrasound (OpUS) is a new paradigm for intracoronary imaging. US is generated at the surface of a fibre optic transducer via the photoacoustic effect. Pulsed or modulated light is absorbed in an engineered coating on the fibre surface and converted to thermal energy. The subsequent temperature rise leads to a pressure rise within the coating, which results in a propagating ultrasound wave. US reflections from imaged structures are received with optical interferometry. With OpUS, high bandwidths (31.5 MHz) and pressures (21.5 MPa) have enabled imaging with axial resolutions better than 50 µm and at depths greater than 20 mm. These values challenge those of conventional 40 MHz IVUS technology and show great potential for future clinical application. Recently-developed nanocomposite coating materials, that are highly transmissive at light wavelengths used for PA and NIRS light, can facilitate multimodality imaging, thereby enabling molecular characterization.